Groundwater quality evaluation for irrigation purposes in wells located in Nirgua, Yaracuy state (Agroindustria, Sociedad y Ambiente, 2022)
The suitability of the water for irrigation purposes was evaluated in fourteen wells located in the Nirgua municipality of Yaracuy state. The water quality was estimated using the Riverside laboratory method, which is based on the risk of salinization and sodification of the soil from the use of irrigation water. In relation to pH, most of the wells evaluated presented values with a tendency towards alkalinity (pH> 7.5). Regarding the total dissolved solids, all the water samples evaluated were classified as fresh water because they presented values Mg2+> Na+, which indicates that it is young waters of recent infiltration into the aquifer. 71% of the wells studied have waters classified as C1S1 and 29% waters type C2S1; in both cases, it is water of excellent quality according to the methodology used to evaluate the aptitude for irrigation purposes.
Keywords: Groundwater quality; agricultural irrigation; SAR